Estimation of non-contact smartphone video-based vital sign monitoring using filtering and standard color conversion techniques - Qayyum, A. (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, vital signs are estimated using smartphone device based video camera imaging technique. The standard color conversion technique and Plane-Orthogonal-to-Skin (POS) algorithm have been applied to estimate the Remote photoplethysmography (rPPG) signal efficiently. Furthermore, the color distortion filtering method is used for pre-processing in order to extract the less noisy YCbCr signal. This rPPG signal could perform better as compared to the standard vital signs estimation methods. The Inter beat interval (IBI) based on maximum peak detection approach has been used for heart rate variability estimation. The results are compared with the ground truth data to compute the accuracy and compared with the existing vital sign monitoring methods. The results show less mean absolute percentage error (MAPE) using our proposed method based on smart phone digital camera than the existing approaches. Â© 2017 IEEE.